(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The field of Internet learning is steadily developing. There are numerous examples that schools can learn from the online learning industry. A new trend emerges in the online learning industry every few years. This study aims to determine the impact of online learning on BSHM students during the pandemic. The online learning platform solves the new homeschooling situation and the associated online distance learning demands. Students usually make their own choices about online or face-to-face programs or courses, which confuses student performance estimates. This study used a descriptive quantitative design involving 50 Bestlink College of the Philippines student respondents. A questionnaire was used to determine the impact of online learning on the students. The questionnaire contained 15 items with five parts and was divided into open-ended and closed-ended questions for students. This research showed the impact of online learning according to the student’s point of view, and the students chose the sample uniquely. This also revealed that online learning is a very accurate solution and type of student education program. They can balance their time by attending virtual classes while doing home activities or wherever they are. It also shows positive results for the students having a hard time schooling. This study aimed to examine how students felt about the impact of online learning based on their own experiences. Students’ perceptions of online education have been determined depending on their experiences. The aspects that influenced those students’ online learning experiences were also examined. The findings of this research will determine the impact of online learning on students who take online classes. Many want online learning to continue studying because it’s easy to access information to comply with the so-called assignments and other activities.